STUDENT COUNCIL EMPOWERMENT AND STUDENT DISCIPLINE IN PUBLIC SECONDARY SCHOOLS IN KISII COUNTY, KENYA - Dorcas Yakhama Adamba; Dr. Viviline Ngeno; Dr. David Ngatia (EPRA International Journal of Environmental Economics Commerce and Educational Management, 2026)
Background: Student councils were introduced in Kenyan public secondary schools to promote student participation and shared responsibility in school governance. However, their formal existence does not necessarily translate into meaningful participation in school management. Limited empirical evidence exists on whether empowering student councils to participate meaningfully in school management is associated with improved student discipline. This study examined the influence of student council empowerment for participation in school management on student discipline in public secondary schools in Kisii County, Kenya. Methods: A mixed-methods approach was employed using a descriptive survey design. The study involved students, student leaders, teachers, and deputy principals in public secondary schools in Kisii County. Quantitative data were collected using structured and semi-structured questionnaires, while qualitative data were obtained through interviews and document analysis. Quantitative data were analysed using descriptive statistics, Pearson correlation, and multiple regression, while qualitative data were analysed thematically. Results: Student council empowerment was very strongly and positively associated with student discipline (r = .890, p < .001). Regression analysis further showed that empowerment significantly predicted student discipline (β = .857, p < .001). Qualitative evidence indicated that leadership training, participation in decision-making, consultation, administrative support, and institutional recognition strengthened student councils' capacity to represent students, mediate conflicts, communicate school expectations, and support positive behaviour. Conclusion: The findings indicate that meaningful student participation in school management depends not only on the existence of student councils but also on the extent to which they are empowered to exercise their responsibilities. Schools should therefore strengthen student leadership development, provide clearly defined mandates, and create structured opportunities for student councils to participate in decisions concerning student welfare and discipline.